Immunological Variables Associated With Clinical and Endoscopic Response to Vedolizumab in Patients With Inflammatory Bowel Diseases. (26th February 2020) - Coletta, Marina; Paroni, Moira; Alvisi, Maria Francesca; De Luca, Matilde; Rulli, Eliana; Mazza, Stefano; Facciotti, Federica; Lattanzi, Georgia; Strati, Francesco; Abrignani, Sergio; Fantini, Massimo Claudio; Vecchi, Maurizio; et al.
Abstract: Background and Aims: Vedolizumab [VDZ] is a monoclonal antibody directed against the α4β7 integrin heterodimer, approved for patients with inflammatory bowel diseases [IBD]. This study aimed at identifying immunological variables associated with response to vedolizumab in patients with ulcerative colitis [UC] and Crohn's disease [CD]. Methods: This is a phase IV explorative prospective interventional trial. IBD patients received open-label VDZ at Weeks 0, 2, 6, and 14. Patients with a clinical response at Week 14 were maintained with VDZ up to Week 54. At Weeks 0 and 14, their peripheral blood was obtained and endoscopy with biopsies was performed. The Week 14 clinical response and remission, Week 54 clinical remission, and Week 14 endoscopic response were evaluated as endpoints of the study. The expression of surface markers, chemokine receptors, and α4β7 heterodimer in peripheral blood and lamina propria lymphocytes was assessed by flow cytometry. A panel of soluble mediators was assessed in sera at baseline and at Week 14 by 45-plex. Results: A total of 38 IBD patients [20 UC, 18 CD] were included in the study. At Week 14, the clinical response and remission rates were 87% and 66%, respectively. Higher baseline levels of circulating memory Th1 cells were strongly associated with clinical response at Week 14 [ p = 0.0001], whereas reduced baseline levels of lamina propria memory Th17 and Th1/17 cells were associated with endoscopic response. Immunological clusters were found to be independently associated with vedolizumab outcomes at multivariable analysis. A panel of soluble markers, including IL17A, TNF, CXCL1, CCL19 for CD and G-CSF and IL7 for UC, associated with vedolizumab-induced Week 54 clinical remission. Conclusions: The results of this exploratory study uncovered a panel of circulating and mucosal immunological variables associated with response to treatment with vedolizumab.